A study on the journey to homicide and offender characteristics in Spain. Issue 2 (18th January 2021) - Santos‐Hermoso, Jorge; Villalba‐García, David; Camacho‐Collados, Miguel; Tejeiro, Ricardo; González‐Álvarez, José L.
Abstract: In this study, the displacement of 687 murderers in Spain (2010–2012) is analysed. The Euclidean distance between the offender's residence and the furthest scene related to the event has been calculated. The analyses showed that the murderers registered a displacement of 0.5 km, with 255 cases of non‐traveller homicide (37.1%). The bivariate analysis found that men, young and foreign, with a criminal record and unrelated to the victim, registered a large distance, as well as multi‐offender homicides and were related to criminal activities. Traveller homicide registered a displacement of 4.3 km, with adults unrelated to the victim travelling the farthest. Multi‐offender and crime‐related homicides continued to show the largest distance. Multivariate analyses showed that if the offender is foreign, has no previous relationship with the victim and there are several offenders involved, the distance will be larger. When only traveller homicides were analysed, only the type of relationship showed significant differences.